Sea urchin waste as valuable alternative source of calcium in laying hens’ diet - Francesca Leone; Michela Sugni; Stefania Marzorati; Silvia Rizzato; Lorenzo Ferrari; Paolo Tremolada; Valentina Ferrante (PLoS ONE, 2025)
Annually, 3000–3500 tons of sea urchins are harvested in the Mediterranean Sea, with only their gonads being consumed (10–30% of the total weight), leaving the rest as waste. This waste, consisting of the skeleton, is rich in biominerals, mainly calcium with a small amount of magnesium, and contains potent antioxidant compounds. Considering the issues of resource overconsumption, and in line with the circular economy concept, this study explored the potential of replacing limestone-derived calcium with sea urchin waste in the diet of laying hens, which require this element to produce eggs. The experiment involved two groups of hens: one receiving a control diet containing limestone-derived calcium, and another fed an experimental diet containing sea urchin waste as alternative source of calcium. Parameters such as egg production, animal welfare, egg quality, and bone breaking strength were assessed. Additionally, the antioxidant activity and carotenoid content of the diets were evaluated, revealing no significant differences between the two groups. Both groups exhibited similar egg production rates; however, the treated group had a lower percentage of discarded eggs and fewer lesions on the head, back, and tail, indicating better animal welfare. The treated group produced eggs with significantly thicker shells, though no significant differences were observed in eggshell weight, breaking strength, ultrastructure. There were also no differences in yolk colour or antioxidant activity between the two groups. Similarly, no significant differences were found in tibia breaking strength, confirming that sea urchin waste can provide bioavailable calcium without compromising bone quality. In conclusion, substituting limestone-derived calcium with sea urchin waste in laying hens’ diets positively affected animal welfare and improved eggshell thickness without compromising egg quality, suggesting that sea urchin waste can be recycled as a valuable alternative to limestone-derived calcium in laying hens’ feed. However, further research is necessary to confirm these findings.